Pemanfaatan Serbuk Kaca sebagai Bahan Tambah dalam Pembuatan Batako - Nursyamsi Nursyamsi; Ivan Indrawan; Ika Puji Hastuty (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
The growing need for adobe bricks as a substitute for lead to an increase in demand for cement as brick-forming material that needs to be done to reduce their use of innovation, one using glass powder. The initial idea of thinking that the chemical elements that exist on the glass some of which are the same as in the cement, the silica (SiO2). This study uses a glass powder as a substitute against the weight of cement. Glass powder used consisted of two types of glass powder passes sieve No. 100 retained on the 200 mesh (BSKø100-ø200) and glass powder escaped sieve No. 200 (BSK <ø200) with six kinds of mixed composition of 0%, 10%, 15%, 20%, 25% and 30%. Analysis of the data by using the provisions of SNI 03-0349-1989. The results showed the entire BSK qualify for the water absorption of solid concrete brick quality I by SNI 03-0349-1989. Visual examination showed BSK surfaces have angled, flat, and free from cracks. BSK0% compressive strength of 95,289kg / cm2 and the compressive strength is highest in BSK <ø200_20% of 91,422kg / cm2 and the quality I belong to the SNI 03-0349-1989. Tensile strength BSK0% of 16,268kg / cm2 and the tensile strength is highest on-ø200 BSKø100 percentage of 15% of 19,464kg / cm2. Overall it is known that BSK <ø200 persentse 20% is the percentage of the nicest to be applied next.